Destruction reconceived: On Winnicott's 'The Use of an Object and Relating through Identifications'. (24th June 2016) - Ogden, Thomas H.
Translations of summary: 'The Use of an Object and Relating through Identifications' is a landmark contribution that I find very difficult to write about because so much of what lies at its core is merely suggested. It is necessary for the reader not only to read the paper, but also to write it. In my reading/writing of the paper, the mother becomes real for the infant in the process of his actually destroying her as an external object (destroying her sense of herself as an adequate mother), and his perceiving that destruction. She also becomes a real external object for the infant in the process of his experiencing the psychological work involved in surviving destruction, a form of work that does not occur in the world of fantasied objects. The analyst or mother may not be able to survive destruction. It is essential that the analyst be able to acknowledge to himself his inability to survive and, if necessary, to end the analysis because of the very damaging effects for both patient and analyst of prolonged experience of this sort. The author presents clinical discussions of analyses in which the analyst survives destruction and is unable to survive destruction.